BUNGA MATAHARI DALAM KARYA SENI GRAFIS CETAK TINGGI - clara maharani; Dyah Yuni Kurniawati (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
The purpose of creating this final work is as a form of aesthetic experience when the author needs calm in living his life. Sunflowers have a philosophy of always following the direction of the sun’s rays, which means being loyal, optimistic and enthusiastic so that sunflowers can be used as an inspiration for those who see them. The issues discussed are: 1) What is interesting about sunflowers as a source of ideas for creating high-print graphic art works, 2) How sunflowers become a theme in high-print graphic art works, 3) How to visualize sunflowers in high-print graphic art works . The objectives of creating this thesis work are: 1) Describe the interesting things about sunflowers, 2) Explain the choice of sunflowers as a source of ideas for creating graphic works of art, 3) Create a visualization of sunflowers as a work of graphic art. Sunflowers are packaged in high-print graphic art visuals with a flow of surrealism and color reduction methods. Presentation of works with figures using matte glass so as not to reflect light. The media used is mdf with a thickness of 3 mm with dimensions of 60 cm x 80 cm. The work is presented by placing it on the surface of the gallery wall using glass figures. Hopefully this work of art can be a reference, useful and enjoyable for the community.